Engrafting human regulatory T cells with a flexible modular chimeric antigen receptor technology. (June 2018) - Koristka, Stefanie; Kegler, Alexandra; Bergmann, Ralf; Arndt, Claudia; Feldmann, Anja; Albert, Susann; Cartellieri, Marc; Ehninger, Armin; Ehninger, Gerhard; Middeke, Jan Moritz; Bornhäuser, Martin; Schmitz, Marc; et al.
Abstract: As regulatory T cells (Tregs) play a fundamental role in immune homeostasis their adoptive transfer emerged as a promising treatment strategy for inflammation-related diseases. Preclinical animal models underline the superiority of antigen-specific Tregs compared to polyclonal cells. Here, we applied a modular chimeric antigen receptor (CAR) technology called UniCAR for generation of antigen-specific human Tregs. In contrast to conventional CARs, UniCAR-endowed Tregs are indirectly linked to their target cells via a separate targeting module (TM). Thus, transduced Tregs can be applied universally as their antigen-specificity is easily adjusted by TM exchange. Activation of UniCAR-engrafted Tregs occurred in strict dependence on the TM, facilitating a precise control over Treg activity. In order to augment efficacy and safety, different intracellular signaling domains were tested. Both 4-1BB (CD137) and CD28 costimulation induced strong suppressive function of genetically modified Tregs. However, in light of safety issues, UniCARs comprising a CD137-CD3ζ signaling domain emerged as constructs of choice for a clinical application of redirected Tregs. In that regard, Tregs isolated from patients suffering from autoimmune or inflammatory diseases were, for the first time, successfully engineered with UniCAR 137/ζ and efficiently suppressed patient-derived effector cells. Overall, the UniCAR platform represents a promising approach to improve Treg-based immunotherapies for tolerance induction. Highlights: Human UniCAR-engrafted Tregs are functionally active in vitro and in vivo . Treg activation occurs in a strict targeting module- and antigen-dependent manner. Tregs endowed with UniCAR 137/ζ or UniCAR 28/ζ are equally suppressive. CD137/ζ signaling does not confer any proinflammatory properties. UniCAR platform enables a precisely controlled and site-specific Treg redirection.